2017
DOI: 10.1088/1361-6463/aa7793
|View full text |Cite
|
Sign up to set email alerts
|

Single channel atmospheric pressure transporting plasma and plasma stream demultiplexing: physical characterization and application toE. colibacteria inactivation

Abstract: In this article, we developed transporting plasma sources that operate at atmospheric pressure. The effect of electrode configuration on plasma transporting was investigated. In order to increase the transporting plasma cross section, we converted a plasma stream into four plasma channels by a cylindrical housing. Electron-excitation and rotational temperatures were estimated using optical emission spectroscopy. Furthermore, the electrical and temporal characteristics of the plasma, discharge power and charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Previous investigations have demonstrated that RONS produced by plasma during treatments with jet or SDBD may play an important role in microbial inactivation 43 , 44 . RONS can induce critical damages to the cell wall, cell membrane, or cellular components.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations have demonstrated that RONS produced by plasma during treatments with jet or SDBD may play an important role in microbial inactivation 43 , 44 . RONS can induce critical damages to the cell wall, cell membrane, or cellular components.…”
Section: Resultsmentioning
confidence: 99%
“…Non-thermal plasma jets at atmospheric pressure are useful tools in many applications [1][2][3][4][5][6][7][8][9][10]. Plasma jets formed from inert feedstock gases (He, Ar, N 2 and their mixtures) are the most popular ones.…”
Section: Introductionmentioning
confidence: 99%